El comercio tardoantiguo (ss.IV-VII) en el noroeste peninsula través del registro cerámico de la Ría de Vigo - Fernández, Adolfo (Roman and late antique Mediterranean pottery, 2014)
This work investigates a large assemblage of potentially late-dated Roman ceramics excavated in the early 1990s during rescue interventions in Vigo (N/E Spain) and its surroundings. It is well established that much of this material originated from the Mediterranean, especially the eastern provinces of the Empire. Based on the analyses of these investigations, this study goes on to assess the extent of the Atlantic distribution route and link the northwest of the Iberian Peninsula well within the trading dynamics of the Mediterranean world